Studi Foraminifera untuk Penentuan Umur dan Lingkungan Pengendapan pada Formasi Sentolo, Desa Geden, Kecamatan Lendah, Kabupaten Kulon Progo, Yogyakarta - Rizqi, Al Hussein Flowers; Thabita Monica Tupang, Kannaya (Retii, 2024)
Stratigraphic measurements measured in the upper part of the Sentolo Formation are very limited, where this formation is mixed with clastic rocks whose distribution is only local and not continuous due to erosion, but in Geden Village, Lendah District, Kulon Progo Regency, Yogyakarta Special Region, an outcrop of the Sentolo formation was found the upper part with a total stratigraphic measurement measuring 5.2 meters. The purpose of this research is to compile the results of the study by obtaining rock samples on measured stratigraphic measurement lines in clastic limestone, with the aim of obtaining data on plangtonic and also bentonic small foraminifera. Based on the results of observations and descriptions, the plangtonic foraminifera found in limestone such as Globorotalia Acostaensis, Globigerinoides ruber, & Globorotalia Margaritae were found to be N16- N17 (Late Miocene), while the benthonic foraminifera found, such as Nodosaria Vetrebralis, Cibicides Polyrraphes, Amphistegina Lessonii, had an environment deposition of Deep Neritic 0-20m – Middle Neritic 20-100m.